1434 : the year a magnificent Chinese fleet sailed to Italy and ignited the Renaissance - Menzies, Gavin (New York : William Morrow, 2008)
The brilliance of the Renaissance laid the foundation of the modern world. Textbooks tell us that it came about as a result of a rediscovery of the ideas and ideals of classical Greece and Rome. But now bestselling historian Gavin Menzies makes the startling argument that in the year 1434, China--then the world's most technologically advanced civilization--provided the spark that set the European Renaissance ablaze. From that date onward, Europeans embraced Chinese intellectual ideas, discoveries, and inventions, all of which form the basis of western civilization today.--From amazon.com.
Setting the scene -- A last voyage -- The emperor's ambassador -- The fleets are prepared for the voyage to the Barbarians -- Zheng He's navigators' calculation of latitude and longitude -- Voyage to the Red Sea -- Cairo and the Red Sea-Nile Canal -- China ignites the Renaissance -- To the Venice of Niccolo Da Conti -- Paolo Toscanelli's Florence -- Toscanelli meets the Chinese ambassador -- Columbus's and Magellan's world maps -- The world maps of Johannes Schoner, Martin Waldseemuller, and Admiral Zheng He -- Toscanell's new astronomy -- The Florentine mathematicians: Toscanelli, Nicholas of Cusa, and Regiomontanus -- Leon Battista Alberti and Leonard Da Vinci -- Leonardo Da Vinci and Chinese inventions -- Leonardo, Di Giorgio, Taccola, and Alberti -- Silk and rice -- Grand canals: China and Lombardy -- Firearms and steel -- Printing -- China's contribution to the Renaissance -- China's legacy -- Tragedy on the high seas: Zheng He's fleet destroyed by a Tsunami -- The conquistadores' inheritance: Our Lady of Victory.
Includes bibliographical references (pages [331]-345) and index.
Keywords: Discoveries in geography -- Chinese; Renaissance; Europe -- Civilization -- Chinese influences